Level of Patient Satisfaction with Mandibular Acrylic Removable Partial Dentures (RPDS) for Different Kennedy Classes: Patient Satisfaction with Dentures - Baloch, Shahzad; Zubair, Samreen; Shaikh, Usman Bashir; Aqsa, .; Qureshi, Ismatullah; Javed, Farhan (Pakistan Journal of Health Sciences, 2025)
Tooth loss affects facial profile, speech, and mastication, limiting social activities. Maintaining oral health involves using prostheses like implants, bridges, and partial dentures, with acrylic polymers being widely used. Various classifications are used for partially edentulous arches, among them Edward Kennedy's classification being the most often accepted. Objective: To assesses patient satisfaction for two months about mandibular Removable Partial Dentures (RPDs) utilizing the Short Assessment of Patient Satisfaction (SAPS) scale from the University of Wollongong's Centre for Health Service Development. Methods: A Cross-sectional observational study was conducted at Outpatient Department (OPD) of prosthodontics, Institute of Dentistry, Liaquat University of Medical and Health Sciences, Jamshoro/Hyderabad. Fifty three patients were selected on Non-probability convenient sampling. Data on comfort, speech, chewing ability, and prosthesis aesthetics were collected at insertion and after two months. The outcomes were categorized using the 5-point rating scale, The Short Assessment of Patient Satisfaction (SAPS). Results: SAPS was significantly differentiated among Kennedy Classifications at the time of insertion, out of 53 patients who were categorized into class 1 to class 4. The mean age of the patients was 39.6 years, 22 patients were very satisfied, 16 satisfied, and 15 not satisfied, with 25 males and 28 females this studies revealed that female patients are more likely to suffer from tooth loss and manage with partial dentures. Conclusion: The majority of patients were satisfied with Mandibular Removable Partial Dentures, with significant differences in SAPS among Kennedy Classifications at insertion and after two months.